Towards a framework for measuring indigenous knowledge systems and practices in mathematics education: An exploratory factor analysis - Hortelano, Julius Ceasar; Ebal Jr., Crispin; Aggabao-Garcia, Princess; Gagaza, Melinda; San Pablo, Generie Mae (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2026)
Indigenous Knowledge Systems and Practices (IKSP) are central to culturally grounded and equitable education; however, their conceptual structure and enactment within mathematics instruction remain difficult to specify and empirically assess. Although culturally responsive education and ethnomathematics frameworks emphasize the integration of Indigenous knowledge, there is a lack of validated measurement tools that capture how IKSP is operationalized in classroom mathematics practices. Addressing this gap, the present study aims to develop and validate an instrument for measuring the enactment of IKSP in mathematics education. Guided by culturally responsive education and ethnomathematics perspectives, an initial pool of 40 items was generated from relevant literature and policy documents within the national Indigenous Peoples Education policy framework. Following expert review, the instrument was administered to 204 Indigenous students in Northern Luzon, Philippines. Exploratory factor analysis using principal axis factoring with promax rotation was conducted to examine the instrument’s underlying structure. The analysis resulted in a refined 16-item scale with a four-factor solution—non-restricting, considering, being cautious, and teaching resource appropriating—accounting for 54.17% of the total variance. The scale demonstrated strong internal consistency (Cronbach’s α = .88). Descriptive findings indicate that students perceive these IKSP-related practices as present in their mathematics learning experiences. The four factors were interpreted as interrelated dimensions of IKSP, yielding an empirically grounded framework that clarifies how Indigenous knowledge is structured and enacted within mathematics instruction. The validated instrument operationalizes this framework through measurable indicators of practice and functions as a diagnostic tool to support teacher reflection and inform the monitoring of Indigenous education policies. Overall, the findings suggest that IKSP in mathematics education is best conceptualized as a multidimensional construct and provide a reference for future research seeking to measure Indigenous knowledge integration in diverse educational contexts.